PERATURAN PEMERINTAH NOMOR 61 TAHUN 2014 TENTANG KEBOLEHAN ABORSI JANIN KASUS PEMERKOSAAN - Rustam Magun Pikahulan; Hajrah Hamuddin (IAIN Ambon, 2020)
The abortion controversy that developed until now is different between countries and between cultures. The Abortion Controversy that occurred in the community involved various parties, both the government and the ulama. The implementation of Government Regulation No. 61/2014 and the MUI fatwa form the basis for obtaining an abortion. The Fatwa of the Indonesian Ulema Council which firmly said that the initial abortion law was haram but in an emergency was permissible. This type of research used by the author in this study is the type of normative legal research, namely legal research conducted by examining library materials, secondary data or library law research. This type of normative legal research is used because the focus of the study in this study is because in this study it will examine the relevance of the MUI Fatwa with Government Regulation No. 61 of 2014 related to the ability of abortion to fetal rape cases. From the results of the analysis it is concluded that the government (PP) No.61 of 2014 concerning obtaining abortion is considered as the first step in protecting women's and reproductive rights. This Government Regulation is in line with MUI Fatwa Number 4 of 2005 which allows the abortion of wombs for reasons that are justified both medically and in Islamic law. Keywords: Abortion, pape, MUI Fatwa.